Suitability and Economics of Grasses for Reclamation and Stabilisation of Mahi Ravines in Gujarat - Verma, Balvir; Singh, Bakhshish; Saraf, N. H.; Monappa, K. (Indian Forester, 1969)
Grasses play an important role in the stabilization of peripheral and contour bunds and bench terrace faces in gullied land reclaimed for cultivation. In the case of deep gullies, where reclamation is very costly, they effectively check the widening and deepening of gullies. The role of grasses for Soil and Water Conservation in ravine lands side by side to their economics has been discussed in this paper.